PENGGUNAAN APLIKASI CANVA UNTUK MENINGKATKAN KREATIVITAS BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK DI SMP ST. ANTONIUS BANGUN MULIA MEDAN - Ambriano Banurea, Zulfi; Erikson Simbolon; Siska Sinaga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the use of the Canva application in improving students’ learning creativity in Catholic Religious Education learning at SMP St. Antonius Bangun Mulia. This study used a qualitative research method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. The informants in this study consisted of Catholic Religious Education teachers and ninth-grade students. The results showed that the use of Canva was able to improve students’ learning creativity through fluency, flexibility, originality, and elaboration thinking skills. In addition, Canva helped create learning activities that were more interesting, interactive, and enjoyable so that students became more active and motivated in participating in the learning process. Teachers were also able to utilize Canva as a digital learning medium that supports the teaching and learning process. The use of Canva in Catholic Religious Education learning had a positive impact on students’ creativity, participation, and self-confidence in presenting their work in front of the class.